If tan (A + B) = p, tan (A – B) = q,


If tan (A + B) = p, tan (A – B) = q, then show that tan 2A = (p + q) / (1 – pq).
[Hint: Use 2A = (A + B) + (A – B)]


We know that,

tan 2A = tan (A + B + A – B)

And also,

$\tan (\mathrm{x}+\mathrm{y})=\frac{\tan \mathrm{x}+\tan \mathrm{y}}{1-\tan \mathrm{x} \tan y}$

$\therefore \tan 2 \mathrm{~A}=\frac{\tan (\mathrm{A}+\mathrm{B})+\tan (\mathrm{A}-\mathrm{B})}{1-\tan (\mathrm{A}+\mathrm{B}) \tan (\mathrm{A}-\mathrm{B})}$

Substituting the values given in question,

$\Rightarrow \tan 2 A=\frac{\mathrm{p}+\mathrm{q}}{1-\mathrm{pq}}$

Hence, $\tan 2 \mathrm{~A}=\frac{\mathrm{p}+\mathrm{q}}{1-\mathrm{pq}}$

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now